Frontiers In Traumatic Brain Injury - Lv, Xianli; Guo, Yi; Mao, Gengsheng (IntechOpen, 2022)
Traumatic brain injury (TBI) has the highest incidence of all common neurological dysfunctions and is a risk factor for a variety of neurological diseases. TBI is a major public health burden and the care of TBI patients is difficult. This book provides a comprehensive overview of TBI, addressing progress and needs in research as well as challenges in treatment. Chapters address such topics as emergency room airway management in TBI, craniocerebral injury in pediatric patients, traumatic optic neuropathy, and more.